Serial Morphologic Changes on Magnetic Resonance Imaging in a Brainstem Tuberculoma after Antituberculous Treatment - George Kovoor; A. Joe Marshal Leo; Kamble J. Harsha; Akash K. George (Indian Journal of Neurosurgery)
Abstract Incidence of tuberculosis (TB) is decreasing all over the world due to improved diagnosis and treatment. Though central nervous system TB accounts for 1% of all TB cases, it carries high mortality and neurologic morbidity. Surgery is difficult when eloquent areas of brain are involved, particularly brainstem. Even with advent of magnetic resonance imaging (MRI) facilities and serologic tests, definitive diagnosis is difficult. We report a case of a 57-year-old-woman with possible brainstem TB, diagnosed based on initial MR images. She was empirically started on anti-TB medications followed by serial repeat MR images at 5, 12, and 19 months interval. The initial MR images revealed a thick ring-enhancing lesion, which showed progressive reduction in size, became irregular thin-walled ring-enhancing lesion at 5 months, uniform ring-enhancing lesion at 12 months, and small solid nodular enhancement at 19 months follow-up. There was gradual improvement in neurologic status, and the patient became asymptomatic at the end of 1 year. Characteristic MRI changes over a period favoring adequate response to antituberculosis treatment aids in strengthening presumptive diagnosis of brainstem tuberculoma in resource-poor countries. Along with presumptive diagnosis and timely initiation of medical therapy, periodic MRI follow-up is important in preventing mortality and reducing morbidity.